Evaluation of Tomato (Solanum lycopersicum L.) Varieties under Different Salt Stress Levels - Sora, Shamil Alo; Belew, Derbew; Etissa, Edossa (International Journal on Food, Agriculture and Natural Resources, 2024)
Tomato is a crop of immense economic importance worldwide and salinity is one of the major abiotic factors limiting its production and productivity in Ethiopia. The study was conducted to assess growth, physiological activities and yield responses of two tomato varieties to six different salinity levels. Evaluation of the varieties for salt tolerance was carried out in greenhouse in 2018/19. Each treatment was replicated three times and arranged in Randomized Complete Block Design in factorial arrangement. Most of the traits showed significant decrease (P<0.0001) as salinity level increased from lower to higher concentration. The highest shoot fresh weight (163.13g/plant), shoot dry matter (32.8g/plant) and leaf area (26.93cm2) were recorded for the control treatment and the highest root fresh weight (12.27g/plant), root dry weight (5.53g/plant) and fruit yield (22.71 tone/ha) were recorded at 1dSm-1for variety Melka Shola, while the lowest shoot fresh weight (79.9g/plant), shoot dry matter (22.67g/plant), leaf area(17.63 cm2), root fresh weight (6.12g/plant) and root dry weight (3.8g/plant)  were recorded at 5 dSm-1  for variety ARP tomato-d2.  The lowest yield (16.73 tone/ha) was recorded at 5 dSm-1 for variety ARP tomato-d2. The highest and the lowest values of photosynthetic rate (0.82 µmolCo2m-2s-1 and (0.47 µmolCo2m-2s-1 respectively) were obtained from the control treatment and the highest salinity level for variety Melka Shola, whereas, corresponding values of (0.84µmolCo2m-2s-1 and 0.56 µmolCo2m-2s-1 were recorded for variety ARP tomato-d2. Results of laboratory analysis showed that, sodium and Na/K significantly increased with increased salinity level. However, potassium, Sulfur and phosphorus showed significant decrease with increasing salinity level.  Melka Shola was found to be more salt tolerant as compared to ARP tomato-d2. Since the present experiment was conducted for one season and under controlled condition, it deserves further evaluation and verification under field condition in salt affected areas and the effect of salinity on tomato quality also deserves further investigation.